Personalised Representation in a Weak and Party-Controlled Legislature: Policy Responsiveness in the French Parliament. (August 2021) - Poyet, Corentin
There is growing interest in personal representation and policy responsiveness in the European literature. The current scholarship mainly focuses on strong legislatures. This article aims to contribute to the discussion about policy responsiveness by investigating the least likely case, France. It asks whether French MPs engage in policy responsiveness, and if they do, how responsiveness interacts with party agenda and electoral vulnerability. Drawing on written parliamentary questions asked by French MPs from 1997 to 2007 ( N = 1172), the article shows that MPs' behaviour is strongly affected by their district features. Moreover, the article shows that party agenda conditions the impact of district features. MPs are more likely to engage in policy responsiveness when the issue is also essential for the party. In other words, policy responsiveness is not independent of the party agenda. The article thus contributes to a better understanding of the personalisation of political representation and its relationship with political parties.